1999
DOI: 10.21273/jashs.124.6.702
|View full text |Cite
|
Sign up to set email alerts
|

Scoparone and Scopoletin Accumulation and Ultraviolet-C Induced Resistance to Postharvest Decay in Oranges as Influenced by Harvest Date

Abstract: `Washington Navel', `Biondo Comune', `Tarocco', and `Valencia Late' orange [Citrus sinensis (L.) Obsek] fruit, harvested at various periods of time, were subjected to ultraviolet-C (UV-C) irradiation at 0.5, 1.5, or 3.0 kJ·m-2 doses and then stored at 7 °C and 90% to 95% relative humidity (RH) for 4 weeks plus one additional week at 20 °C and 80% RH. Following UV-C treatment, there was varying amounts of rind browning and necrotic peel damage, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…Applying a potentially harmful agent such as UV‐C radiation, at appropriate intensities and doses, has been reported to induce some beneficial physiological responses (Shama and Alderson 2005). Accumulation of the phytoalexins scopoletin and scoparone has been found in UV‐C‐treated citrus fruit (D’Hallewin and others 1999). Increases in the activity of enzymes associated with the metabolism of phenolic compounds, such as phenylalanine ammonia‐lyase (PAL) and polyphenol oxidase (POD), may also contribute to reduce the susceptibility against pathogens in irradiated fruits (Pombo and others 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Applying a potentially harmful agent such as UV‐C radiation, at appropriate intensities and doses, has been reported to induce some beneficial physiological responses (Shama and Alderson 2005). Accumulation of the phytoalexins scopoletin and scoparone has been found in UV‐C‐treated citrus fruit (D’Hallewin and others 1999). Increases in the activity of enzymes associated with the metabolism of phenolic compounds, such as phenylalanine ammonia‐lyase (PAL) and polyphenol oxidase (POD), may also contribute to reduce the susceptibility against pathogens in irradiated fruits (Pombo and others 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In treated plant tissues, chemical species with beneficial effects on human health can be induced (LagunasSolar et al 2006;Shama 2007;. These substances include phytoalexins such as scoparone in oranges (Dhallewin et al 1999), 6-methoxymellein in carrots (Mercier et al 2000), and resveratrol in grapes, with a number of cardioprotective properties (Cantos et al 2002). Enzymes such as chitinases and glucanases in peaches (El Ghaouth et al 2003) and tomatoes are also induced (Barka 2001).…”
Section: Solid Foods Of Vegetable Originmentioning
confidence: 99%
“…Inducible resistance, especially with radiation at 254 nm, was related to the biosynthesis of substances (mainly phenols) toxic to the pathogens, induced by an increase in the activity of biosynthetic enzymes such as phenylalanine ammonia‐lyase (Frietzenheimer & Kindl, 1981). D’hallewin et al . (1999) found that the increases of scoparone and scopoletin in citrus fruit by UV‐C irradiation may be related with the resistance induced against pathogens.…”
Section: Introductionmentioning
confidence: 99%